Correlated metadiscourse and metacognition in writing research articles: A cross-linguistic and cross-cultural study - Gai, Fei-Hong; Wang, Yao (Frontiers in Psychology, 2022)
Metadiscourse represents a producer’s intention to guide a receiver’s interpretation of the textual meanings. It is a highly dynamic topic in discourse analysis and language education. Related studies provide a way to understand language in use, and contribute to a better understanding about the relationship between the seemingly unconscious language choices and the social contexts. Based-on a corpus of 150 research articles (RAs) written by English L1 scholars, Chinese ESL scholars and Chinese L1 scholars, this study compared their interactive and interactional metadiscourse strategies cross-linguistically and cross-culturally. Quantitative results manifest significantly higher metadiscursive frequencies in English-medium RAs than in Chinese-medium RAs, and significantly higher metadiscursive frequencies in RAs written by British-American scholars than by Chinese scholars. Also, Chinese ESL writers reveal L1-based transfer of discourse conceptualization. Apart from providing with cultural explanations, this study then particularly discusses cognitive implications of culture-specific and language-specific metadiscourse variations by addressing the connections between metacognition and metadiscourse. With the proposed Model of Correlated Metadiscourse and Metacognition, it argues that metadiscourse is the linguistic reflection of metacognition and that metacognition exerts mediation and monitoring over cognitive objects partly by the means of metadiscourse.